Characteristics of Nanophase WC and WC-3 wt% (Ni, Co, and Fe) Alloys Using a Rapid Sintering Process for the Application of Friction Stir Processing Tools - Daeup Kim; Young Choi; Yongil Kim; Seungboo Jung (Advances in Materials Science and Engineering)
Microstructures and mechanical characteristics of tungsten carbide- (WC-) based alloys, that is, WC, WC-3 wt% Ni, WC-3 wt% Co, and WC-3 wt% Fe, fabricated using a spark plasma sintering (SPS) method for the application of friction stir processing tools were evaluated. The sintered bodies with a diameter of 66 mm showed relative densities of up to 99% with an average particle size of 0.26~0.41 μm under a pressure condition of 60 MPa with an electric current for 35 min without noticeable grain growth during sintering. Even though no phase changes were observed after the ball milling process the phases of W2C and WC1-x appeared in all sintered samples after sintering. The Vickers hardness and fracture toughness of the WC, WC-3 wt% Ni, WC-3 wt% Co, and WC-3 wt% Fe samples ranged from 2,240 kg mm2 to 2,730 kg mm2 and from 6.3 MPa·m1/2 to 9.1 MPa·m1/2, respectively.